Literacy-based tex books to improve the character and language competence of elementary students - Dwi Agus Setiawan Setiawan; Farida Nur Kumala; Tamella Tamella (Universitas Kanjuruhan Malang, 2023)
The purpose of this study was to produce and determine the feasibility, practicality, and legibility of reading literacy-based textbooks using the type of research and development of the 4D model. The research instruments were arranged based on the level of research needs, namely material expert validation, product validation, and linguist validation. The results of the product feasibility assessment by validation experts obtained 95.8% media validation, 95% material validation, and 91.96% language validation. The product readability rating obtained 89.83%, supported by 90.75% language literacy story questions and 89% character-based language story test results. The findings of this study indicate that reading literacy-based textbooks can attract students' attention and are interactive, the presentation of the content supported by pictures and various color compositions can attract reading interest and stimulate critical thinking skills. So as to help students have the literacy skills needed at this time.